Annealing Heat Treatment of ZnO Nanoparticles Grown on Porous Si Substrate Using Spin-Coating Method. (4th February 2014) - Eswar, K. A.; Rouhi, J.; Husairi, H. F.; Rusop, M.; Abdullah, S.
Abstract : ZnO nanoparticles were successfully deposited on porous silicon (PSi) substrate using spin-coating method. In order to prepare PSi, electrochemical etching was employed to modify the Si surface. Zinc acetate dihydrate was used as a starting material in ZnO sol-gel solution preparation. The postannealing treatments were investigated on morphologies and photoluminescence (PL) properties of the ZnO thin films. Field emission scanning electron microscopy (FESEM) results indicate that the thin films composed by ZnO nanoparticles were distributed uniformly on PSi. The average sizes of ZnO nanoparticle increase with increasing annealing temperature. Atomic force microscopic (AFM) analysis reveals that ZnO thin films annealed at 500°C had the smoothest surface. PL spectra show two peaks that completely correspond to nanostructured ZnO and PSi. These findings indicate that the ZnO nanostructures grown on PSi are promising for application as light emitting devices.